Health And Research Journal:A new Beggining - Marvaki, Christina (Health & Research Journal, 2019)
2019: it was a joint decision of the journal’s Editorial Board, to change the language from Greek to English. The Greek language is the language that is appreciated and recognized internationally as the language with an amazing and unique wealth. This change has one purpose and that is, to OPEN “out of borders”, a movement that will provide and secure opportunities of international prospect. Three years ago, in 2015, we decided to publish the HEALTH and RESEARCH JOURNAL, with the aim of publishing all MSc dissertations of postgraduate students. Today we believe that this goal needs to be modified. The journal, besides the Master’s Program "Intensive Care Units" (which is the main publisher), collaborates and supports the Master’s Program of “Clinical and Experimental Neurosurgery”, the Master’s Program of “Hellenic Society for Ergospirometry, Exercise and Rehabilitation” and the “Hellenic Society of Nursing Research and Education” which is the co-publisher. The road has already been opened and in the near future our journal will collaborate with the National Documentation Center, which will give new prospect. We hope that this change will receive the acceptance and consent we expect. Value, reliability and scientific approach depend on the entire scientific community that will decide to participate by publishing their manuscripts. We hope the new year to bring something new to HEALTH and RESEARCH JOURNAL and to make it equal to many remarkable and reputable scientific journals. Happy New Year with peace, health and scientific achievements. The Editorial Board